APPLICATION OF THE FINITE ELEMENT METHOD TO INVESTIGATE THE IMPACT OF FRONTAL COLLISIONS ON THE DRIVER OF A 29-SEAT PASSENGER BUS: APPLICATION OF THE FINITE ELEMENT METHOD TO INVESTIGATE THE IMPACT OF FRONTAL COLLISIONS ON THE DRIVER OF A 29-SEAT PASSENGER BUS - Quan, Vu Hai; Quang Tam, Tran; Anh Ngoc, Nguyen; Xuan Hien, Nguyen (Journal of Applied Engineering Science, 2025)
Passenger buses are widely used across all countries, operating at high frequencies and speeds. This study analyzes the effects of frontal collisions on the driver of a 29-seat passenger bus, using the UN/ECE R29 regulation as the crash test condition. Additional evaluation standards were also integrated to assess the driver’s injury risks during the simulation, which was conducted using the finite element method. Results indicate that in the baseline (non-improved) bus configuration, the intrusion into the driver’s cabin reached 510 mm. The impact on the driver’s right femur recorded a peak force of 2976.3 N, while the neck sustained a maximum bending moment of 53108.12 Nmm. However, after incorporating an energy-absorbing crash box, significant improvements were observed. The intrusion depth was reduced by 16.88% to 424.167 mm. The force transmitted to the right femur decreased by 31.13%, with a new peak value of 2049.6 N, and the maximum neck bending moment dropped by 14.14% to 45594.26 Nmm. These results demonstrate that the addition of an energy-absorbing beam significantly enhances the frontal crash safety performance of the 29-seat passenger bus, particularly in reducing the injury risks to the driver.